INNV-19. THE DETECTION OF DISSEMINATED PINEAL PARENCHYMAL TUMOR OF INTERMEDIATE DIFFERENTIATION (PPTID) IN CEREBROSPINAL FLUID (CSF) USING CELL CAPTURE AND IMMUNOCYTOCHEMISTRY. (14th November 2022) - Armijo, Kaitlyn; Sweed, Nathan; Hsiao, Steven; Pircher, Tony; Marrin, Mikayla; Cho, Leslie; Kreitzburg, Kelly; Blouw, Barbara; Fisher, Deanna; Dugan, Michael; Kesari, Santosh
Abstract: BACKGROUND: Pineal parenchymal tumors of intermediate differentiation (PPTID) account for 21% to 54% of pineal parenchymal tumors and may be complicated by cerebrospinal dissemination (most commonly at time of reoccurrence; up to 4-10 years post resection). The integral membrane protein synaptophysin is expressed in neuroendocrine cells and virtually all neuraxial neurons that contribute to synaptic transmission. PPTID frequently demonstrates synaptophysin independently of other neural differentiation markers. Cerebrospinal fluid (CSF) cell capture assays have demonstrated utility for assessing disseminated intracranial neoplasms, thus we explore this technology for monitoring a patient with PPTID. METHODS: A 30-year-old female patient with PPTID diagnosed two years prior was suspected for intracranial dissemination and underwent five CSF collections over the course of 64 days. Per collection, approximately 7 mL of CSF was submitted for each cytology and cell capture. Cytology was performed at Providence Saint John's Health Center. The CNSide™ platform (Biocept, Inc.) was used to capture and stain cells for DAPI, synaptophysin, and CD45. Multiple capture antibody cocktails (termed 1986, 1822, and gTP1—originally developed for use in carcinoma, melanoma, and glioma) were tested. Cells of interest (COI) were defined by positive immunoreactivity for both DAPI and synaptophysin and no immunoreactivity for CD45. Results were quantified and compared longitudinally. RESULTS: CSF analysis on days 0, 9, 21, 36, and 64 demonstrated negative results by cytology and 51, 96, 170, 130, and 43 COI/mL by the CNSide platform, respectively. Cumulative mean capture rates for cocktails 1986, 1822, and gTP1 were 47, 14, and 36 COI/mL/sample, respectively. DISCUSSION: A significant amount of PPTID patients will develop cerebrospinal dissemination. The importance of craniospinal control in this setting has been previously demonstrated. Our work suggests that cell capture assays paired with immunocytochemistry can be used as sensitive means to monitor disseminated PPTID and may impact treatment decisions.